2022
DOI: 10.1186/s12987-022-00320-4
|View full text |Cite
|
Sign up to set email alerts
|

Parasagittal dural space and cerebrospinal fluid (CSF) flow across the lifespan in healthy adults

Abstract: Background Recent studies have suggested alternative cerebrospinal fluid (CSF) clearance pathways for brain parenchymal metabolic waste products. One fundamental but relatively under-explored component of these pathways is the anatomic region surrounding the superior sagittal sinus, which has been shown to have relevance to trans-arachnoid molecular passage. This so-called parasagittal dural (PSD) space may play a physiologically significant role as a distal intracranial component of the human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 34 publications
2
23
1
Order By: Relevance
“…Both increasing age and male sex correlated positively with PSD volume, consistent with earlier findings 25,26 . Patients with AD had less visible intradural channels compared to younger non-AD individuals in a limited post-mortem study 21 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both increasing age and male sex correlated positively with PSD volume, consistent with earlier findings 25,26 . Patients with AD had less visible intradural channels compared to younger non-AD individuals in a limited post-mortem study 21 .…”
Section: Discussionsupporting
confidence: 90%
“…The method to segment PSD is not a standardised procedure. Two previous studies 25,26 used different protocols to examine and segment PSD and the resulting volumes are not comparable. However, we used the same scanner, coil, protocol, and segmentation method to achieve comparable results within this study, even if the volumes per se are not directly comparable with other studies.…”
Section: Methodsmentioning
confidence: 97%
“…Two studies have previously identified agerelated increases in the volume of the PSD. 40,41 As such, one hypothesis for our finding is that overall flow metrics are decreased due to increasing volume of the CSF and ISF space, leading to increased stagnation and reduced relative waste clearance. In an another work, Taoka et al demonstrated age-dependent intrinsic decreased diffusivity of the perivascular and perivenous space using diffusion weighted image analysis along the perivascular space (DWI-ALPS), 42 with further studies also demonstrating decreased diffusivity in the setting of mild cognitive impairment and Alzheimer's disease.…”
Section: Discussionmentioning
confidence: 82%
“…Work from Hett et al focused on quantifying more distal components of the brain's waste clearance system in the parasagittal dural space (PSD), finding that PSD volume increased with age and maximum bidirectional CSF flow through the aqueduct. 41 It is important to note the opposite CSF flow sign convention used between Hett and colleagues and this study. Future work should focus on developing noninvasive methods and post-processing techniques to accurately visualize and quantify remaining components of the brain's waste clearance system.…”
Section: Discussionmentioning
confidence: 92%